Sequence and structure requirements for Drosophila tRNA 5'- and 3'-end processing. - Levinger, L.; Vasisht, V.; Greene, V.; Bourne, R.; Birk, A.; Kolla, S. (Journal of Biological Chemistry, 1995)
Eukaryotic tRNAs are processed at their 5'- and 3'- ends by endonucleases RNase P and 3'-tRNase, respectively. We have prepared substrates for both enzymes, separated the activities from a Drosophila extract, and designed variant tRNAs to assess the effects of sequence and structure on processing. Mutations affect these reactions in similar ways; thus, RNase P and 3'-tRNase probably require similar substrate structures to maintain the catalytic fit. RNase P is more sensitive to substrate substitutions than 3'-tRNase. In three of the four stems, one substitution prevents both processing reactions while the opposite one has less effect; anticodon stem substitutions hardly affect processing, and double substitution intended to restore base pairing also restore processing to the wild type rate. Structure probing suggests that tRNA misfolding sometimes coincides with reduced processing. In other cases, processing inhibition probably results from specific unfavorable stem appositions leading to local helix deformation. A single T loop substitution disrupts the tertiary D-T loop interaction and reduces processing. We have thus begun mapping tRNA processing determinants on the global, local, and tertiary structure levels.